A study of the effects of climate change and human activities on NPP of marsh wetland vegetation in the Yellow River source region between 2000 and 2020 - Feng, Xueke; Zhao, Zhizhong; Ma, Tao; Hu, Bixia (Frontiers in Ecology and Evolution, 2023)
Quantitative assessment of the impacts of climate change and human activities on marsh wetland is essential for the sustainable development of marsh wetland ecosystem. This study takes the marsh wetland in the Yellow River source region (YRSR) as the research object, using the method of residual analysis, the potential net primary productivity (NPPp) of marsh wetland vegetation in the YRSR between 2000 and 2020 was stimulated using the Zhou Guangsheng model, and the actual primary productivity (NPPa) of marsh wetland vegetation was download from MOD17A3HGF product, and the difference between them was employed to calculate the NPP affected by human activities, the relative contribution of climate change and human activities to the change of NPPa of marsh wetland vegetation was quantitatively evaluated. The results revealed that between 2000 and 2020, NPPa of marsh wetland vegetation increased in the YRSR by 95.76%, among which climate-dominated and human-dominated NPP change occupied by 66.29% and 29.47% of study areas, respectively. The Zoige Plateau in the southeast accounted for the majority of the 4.24% decline in the NPPa of the marsh wetland vegetation, almost all of which were affected by human activities. It is found that the warming and humidifying of climate, as well as human protective construction activities, are the important reasons for the increase of NPPa of marsh wetland vegetation in the YRSR. Although climate change remains an important cause of the increase in NPPa of marsh wetland vegetation, the contribution of human activities to the increase in NPPa of marsh wetland vegetation is increasing.